2010
DOI: 10.1007/s13149-010-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

Méningoencéphalite à Morganella morganii : à propos d’un cas

Abstract: A central nervous system infection due to Morganella morganii is uncommon. We report a case diagnosed at the neurological department of Fann teaching hospital in Dakar, Senegal. A 12-year-old boy was hospitalized for acute meningoencephalitis. The CT scan was normal and the study of cerebrospinal fluid (CSF) revealed cytological and biochemical abnormalities and M. morganii. HIV and syphilitic serologies were negative and blood CD4 lymphocyte count showed 354 per mm(3). The treatment with cefotaxime associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Contrary to this study, Mahrouki et al () identified bla DHA‐1 in class‐1 integrons in M. morganii in clinical specimens collected between 2004 and 2009 in Tunis, Tunisia, which also harbored qnrA6 and aac ( 6' ) ‐Ib‐cr quinolone resistance determinants (Mahrouki et al ). Ndiaye et al () also reported on a M. morganii isolate from the cerebrospinal fluid of a 12‐year old boy with acute meningoencephalitis in Dakar, Senegal (Ndiaye et al ), confirming the presence of this opportunistic pathogen in African healthcare settings. Nevertheless, a whole‐genome analysis of M. morganii from Africa is non‐existent.…”
Section: Resultsmentioning
confidence: 81%
“…Contrary to this study, Mahrouki et al () identified bla DHA‐1 in class‐1 integrons in M. morganii in clinical specimens collected between 2004 and 2009 in Tunis, Tunisia, which also harbored qnrA6 and aac ( 6' ) ‐Ib‐cr quinolone resistance determinants (Mahrouki et al ). Ndiaye et al () also reported on a M. morganii isolate from the cerebrospinal fluid of a 12‐year old boy with acute meningoencephalitis in Dakar, Senegal (Ndiaye et al ), confirming the presence of this opportunistic pathogen in African healthcare settings. Nevertheless, a whole‐genome analysis of M. morganii from Africa is non‐existent.…”
Section: Resultsmentioning
confidence: 81%
“…In a review of the literature, there are 12 prior reports of M. morganii intracranial infections, with all prior described cases being parenchymal abscesses or meningitis. [ 1 , 2 , 7 , 8 , 10 - 17 ] Here, we report the first case description of isolated SE caused by M. morganii .…”
Section: Discussionmentioning
confidence: 94%
“…[ 6 ] This bacterial species is only rarely associated with central nervous system infections, with only 12 documented cases of brain abscesses and meningitis caused by M. morganii . [ 1 , 2 , 7 , 8 , 10 - 17 ] Two of these reported patients had coexistent SE secondary to the primary infection, but isolated SE cause by M. morganii has not been previously reported [ Table 1 ]. Here, we present a case of an isolated SE caused by M. morganii in a previously healthy, immunocompetent 13-month-old female.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of the reported studies in the literature, including our case, was 27.8%. The most common presentation was meningitis, with 10 cases; 5 cases were isolated meningitis, 7 8 9 10 11 2 were combined with brain abscesses, 3 12 1 was combined with subdural empyema, 13 1 was combined with encephalitis, 14 and 1 was combined with sepsis. 15 The second most common presentation was brain abscess, with seven cases; five cases were isolated brain abscesses, 5 16 17 18 two cases were combined with meningitis, 3 12 and one case was combined with subdural empyema.…”
Section: Discussionmentioning
confidence: 99%